The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/ajh.21504
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of 122 pregnancies in essential thrombocythemia patients: A report from the Italian registry

Abstract: Pregnancy is a high-risk event in women with essential thrombocythemia (ET). This observational study evaluated pregnancy outcome in ET patients focusing on the potential impact of aspirin (ASA) or interferon alpha (IFN) treatment during pregnancy. We retrospectively analyzed 122 pregnancies in 92 women consecutively observed in the last 10 years in 17 centers of the Italian thrombocythemia registry (RIT). The live birth rate was 75.4% (92/122 pregnancies). The risk of spontaneous abortion was 2.5-fold higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
2
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 25 publications
6
72
2
9
Order By: Relevance
“…73 The pathogenesis of these complications is unclear; age, parity, thrombophilia, PLT count, WBC count, and hemoglobin level have not been found to be predictive of pregnancy outcome in ET. [74][75][76] Whether the use of aspirin can improve pregnancy outcome is uncertain [74][75][76][77] ; however, a meta-analysis of randomized trials conducted outside ET concluded that low-dose aspirin is effective in preventing preeclampsia, being safe for both mother and fetus. 78 Pregnancy complications in women with ET are associated with a higher risk of subsequent thrombosis.…”
Section: Distinguishing Familial Et From Hereditary Thrombocytosismentioning
confidence: 99%
“…73 The pathogenesis of these complications is unclear; age, parity, thrombophilia, PLT count, WBC count, and hemoglobin level have not been found to be predictive of pregnancy outcome in ET. [74][75][76] Whether the use of aspirin can improve pregnancy outcome is uncertain [74][75][76][77] ; however, a meta-analysis of randomized trials conducted outside ET concluded that low-dose aspirin is effective in preventing preeclampsia, being safe for both mother and fetus. 78 Pregnancy complications in women with ET are associated with a higher risk of subsequent thrombosis.…”
Section: Distinguishing Familial Et From Hereditary Thrombocytosismentioning
confidence: 99%
“…Anecdotal use of Peg-IFNa in pregnant patients with hepatitis or myeloproliferative disorders (including ET) has been reported with encouraging results concerning safety and disease remission [53][54][55][56][57].…”
Section: Pegylated Interferon-amentioning
confidence: 99%
“…7 The benefit of low-dose aspirin (ASA) is contradictory, with some studies suggesting a reduction of miscarriage in treated patients 6 and others not. 8 However, safety of ASA in this population is well established.…”
mentioning
confidence: 99%
“…However, one retrospective study reported safety for IFN-treated pregnant patients with an increase in live birth rate, 8 and current recommendations consider IFN as a reasonable treatment.…”
mentioning
confidence: 99%